Vitamin D Status and the Risk of Anemia in Community-Dwelling Adults: Results from the National Health and Nutrition Examination Survey 2001–2006. Issue 50 (December 2015) - Monlezun, Dominique J.; Camargo, Carlos A.; Mullen, John T.; Quraishi, Sadeq A.
Abstract : Abstract: Low vitamin D status has been implicated in several chronic medical conditions and unfavorable health outcomes. Our goal was to investigate whether serum 25-hydroxyvitamin D (25OHD) levels are a potentially modifiable risk factor for anemia in a nationally representative cohort of community-dwelling individuals in the United States. We performed a cross-sectional study of 5456 individuals (≥17 years) from the National Health and Nutrition Examination Survey from 2001 to 2006. Locally weighted scatterplot smoothing (LOWESS) was used to graphically depict the relationship between serum 25OHD levels and the cumulative frequency of anemia. Multivariable logistic regression models were then used to assess the independent association of 25OHD levels with anemia, while controlling for age, sex, race, body mass index, chronic kidney disease, as well as serum levels of C-reactive protein, ferritin, iron, vitamin B12, and folic acid. The mean (standard error) 25OHD and hemoglobin levels in the analytic group were 23.5 (0.4) ng/mL and 14.4 (0.1) g/dL, respectively. Prevalence of anemia was 3.9%. Locally weighted scatterplot smoothing analysis demonstrated a near-linear relationship between vitamin D status and cumulative frequency of anemia up to 25OHD levels of approximately 20 ng/mL. With increasing 25OHD levels, the curve flattened out progressively. Multivariable regression analysis demonstrated an inverse association of 25OHD levels with the risk of anemia (adjusted odds ratio 0.97; 95% confidence interval 0.95–0.99 per 1 ng/mL change in 25OHD). Compared to individuals with ≥20 ng/mL, individuals with 25OHD levels <20 ng/mL were more likely to be anemic (adjusted odds ratio 1.64; 95% confidence interval 1.08–2.49). In a nationally representative sample of community-dwelling individuals in the United States, low 25OHD levels were associated with increased risk of anemia. Randomized controlled trials are needed to determine whether optimizing vitamin D status can reduce the burden of anemia in the general population.